PENGARUH KECERDASAN EMOSIONAL, KECERDASAN INTELEKTUAL DAN MINAT BELAJAR TERHADAP TINGKAT PEMAHAMAN AKUNTANSI PADA MAHASISWA TINGKAT AKHIR JURUSAN AKUNTANSI: Emotional Intelligence; Intellectual Intelligence; Learning Interest; Accounting Comprehension - MARTUA YEHEZKIEL LUMBAN TOBING, RIDHO; Azmiana, Risca (LPPM Universitas Putera Batam, 2024)
This study looks at how emotional intelligence, intellectual intelligence, and learning interest affect accounting understanding at Universitas Riau Kepulauan, Universitas Internasional Batam, Universitas Ibnu Sina, Universitas Batam, and Universitas Universal. The research population consists of 1,475 students, and data was collected through an online survey using Google Forms. A total of 165 respondents were selected using purposive sampling with the Slovin formula. The questionnaire questions were evaluated with a Likert scale, and the data was analyzed using IBM SPSS Version 25. The study includes descriptive statistics, validity-reliability tests, classical assumptions, multiple linear regression, and both partial and simultaneous hypothesis testing. The results show that emotional intelligence mostly doesn’t have a significant effect on accounting understanding, while intellectual intelligence and learning interest do have a significant partial effect on accounting understanding. Overall, all three factors collectively affect accounting understanding. The Adjusted R Squared value of 28.6% indicates that emotional intelligence, intellectual intelligence, and learning interest influence accounting understanding